Effect of Cr Addition on Properties and Tribological Behavior at Elevated Temperature of Boride Layers Grown on Borosintered Powder Metallurgy Alloys - Gunen, Ali; Bolukbasi, Omer Saltuk; Ozgurluk, Yasin; Ozkan, Dervis; Odabas, Okan; Somunkiran, Ilyas (Korean Inst Metals Materials, 2023)
This study focused on chromium addition (0 wt%, 3 wt%, 6 wt%, 9 wt% and 12 wt%) on the boride layer formation, microhardness, fracture toughness and elevated temperature friction and wear behaviour of alloys formed by powder metallurgy (P/M). The boride layers obtained on P/M alloys were characterized by examining density, porosity, surface roughness, scanning electron microscopy, energy-dispersive X-ray spectroscopy, X-ray diffraction, surface profilometry, microhardness, and fracture toughness. The addition of Cr has a significant effect on both boride layer formation and friction-wear behaviour of P/M alloys. Increasing the Cr addition up to 6 wt% has an improving effect on the microhardness, fracture toughness and wear resistance of the P/M alloys, whereas in the case of 9-12 wt% Cr addition causes exfoliation in the boride layer and low fracture toughness, thus reducing wear resistance. Coefficients of friction and wear volume losses at elevated temperatures are higher than room temperature. The best wear resistance at room temperature was obtained in the sample containing 3 wt% Cr with the highest fracture toughness, while the best wear resistance at 250 degrees C and 500 degrees C was obtained in the sample containing 6 wt% Cr, where the highest hardness value was obtained.
Keywords: Sintering; Boronizing; High-temperature wear; Friction; Powder metallurgy